MENTALITAS AVOS’ DALAM FILM IRONIYA SUD’BY ILI S LYODKIM PAROM (IRONI TAKDIR, ATAU NIKMATI SAUNAMU)(1976) KARYA ELDAR ALEKSANDROVICH RYAZANOV - Laelasari, Septifa; Widyastuti, Thera (Multikultura, 2025)
This study discusses the Avos’ mentality character possessed by Russian society, which is implicitly portrayed through the film Ирония Судьбы Или С Лёдким Паром (Ironi Takdir, Atau Nikmati Saunamu) by Eldar Aleksandrovich Ryazanov (1976). The purpose of this research is to identify the forms of characteristics that represent the Avos’ mentality in the film. The research method used is expository and descriptive-critical analysis. Roland Barthes’ semiotic theory (denotation and connotation) is applied to uncover the signs in the film that implicitly reveal the characteristics of the Avos’ mentality. These signs indicate traits of the Avos’ mentality, such as a tendency to resist change, a preference for discussing the past rather than planning for the future, spontaneous actions, and reliance on luck or supernatural assistance.